DEVELOPMENT OF MATHEMATICS LEARNING TOOLS BASED ON COGNITIVE CONFLICT STRATEGIES TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - I Gusti Bagus Jayantha; I Nengah Suparta; I Gusti Putu Sudiarta (Universitas Muhammadiyah Makassar, 2023)
Learning tools on triangular and quadrilateral materials are very important because they serve as a benchmark for learning success. The low critical thinking ability in Grade VII mathematics suggests that the media used has not been optimized and has limitations. This study aimed to determine the characteristics and applications of mathematics learning tools that incorporate cognitive conflict strategies on triangular and quadrilateral materials that are valid, practical, and effective in improving students' critical thinking skills. The research used an RD design, and the study was conducted in the fall semester of the 2021/2022 academic year in grade VII of SMP Negeri 2 in Gerokgak. The Plomp device development model is applied in three stages: preliminary research, prototyping, and assessment. A study found that using triangular and quadrilateral learning tools with cognitive conflict strategies in grade VII SMP Negeri 2 Gerokgak improved math critical thinking skills. The student books presented challenging problems, had conflict discussions, and gave feedback. The teacher manuals included tasks to solve problematic scenarios and evaluate students. These tools are effective and practical, and can replace traditional teaching methods.